PRELIMINARY OBSERVATION OF TROPICAL DIATOM Thalassiosira spp. FROM TELUK BAHANG, PENANG - Aysha Javeed; Sazlina Salleh; Aqilah Darif; Mahadi Mohammad (Scripta Biologica, 2018)
This study describes the morphological structure of Thalassiosira spp. found in coastal water and intertidal area of Teluk Bahang, Penang. Examination of the samples collected from January 2015 to June 2016 showed that these species were the common genera in both benthic and surface seawater at Teluk Bahang. To obtain phytoplankton samples, five liters of seawater were filtered through the plankton net (35 µm). While for benthic samples, the samples were collected at sediment surface of 1 mm depth. Samples of Thalassiosira spp. were obtained from both phytoplankton and benthic samples. Scanning electron microscope (SEM) was used to study the morphology of Thalassiosira spp. Results from the SEM showed distinct differences in areolae pattern, sizes, position and number of processes among Thalassiosira spp. (Thalassiosira nanolineata, Thalassiosira densannula, and Thalassiosira gravida). Thalassiosira densannula and Thalassiosira nanolineata were found in both habitats, coastal and benthic area while Thalassiosira gravida was found only in coastal water. Thalassiosira spp. contribute approximately 15% of the total benthic community and approximately 35% of the total phytoplankton community.